Canonization and decanonization - Kooij, Arie van der 1945-; Toorn, K. van der; Snoek, Joannes Augustinus Maria 1946- (Studies in the history of religions, 1998)
This volume is the most wide-ranging religio-historical study on (de)canonization ever published. It contains significant contributions to the study of canonization in different religions in ancient times as well as in modern societies. An Annotated Bibliography adds greatly to its value.